Clear cell adenocarcinoma of ureter: A case report with immunohistochemical study - Tadashi Terada, M.D., Ph.D (Elsevier, 2016)
The author reports herein the fourth case of rare clear cell adenocarcinoma (CCA) of ureter. The present case is the first of ureter CCA with extensive immunohistochemical examination. The patient is a 61-year-old man. The CCA was composed of malignant cells with very clear ample cytoplasm with occasional glandular formations. No apparent hobnail cells were seen. The tumor cells were seen to invade the adventitia. No carcinoma in situ was seen in the surrounding urothelium. A lymph showed metastasis. Histochemical stains revealed that the clear cytoplasm was due to glycogen not mucins or lipids. Immunohistochemically, tumor cells were positive for cytokeratin (CK) AE1/3, CK CAM5.2, CK34BE12, CK8, CK18, EMA, CEA, CA19-9, p53, platelet-derived growth factor-α (PDGFRA), MUC-1, and Ki-67 (labeling index = 26%). The tumor cells were negative for CK5/6, CK7, CK14, CK19, CK20, NSE, p63, vimentin, S100 protein, α-smooth muscle actin, c-erbB2, chromogranin, synaptophysin, KIT (CD117), CD56, CDX-2, MUC2, MUC5AC, MUC6, CD10 and RCC markers.